2013
DOI: 10.1177/0042098013483603
|View full text |Cite
|
Sign up to set email alerts
|

Viva la Raza! A Park, a Riot and Neighbourhood Change in North Denver

Abstract: People reside in homes; however, they live in neighbourhoods comprised of parks, sidewalks, restaurants, shops and other everyday places. Whether current or potential neighbourhood residents feel at home in these places remains an undertheorised aspect of neighbourhood change. Rather than housing policy or real estate development, this essay explores public space as a mechanism of neighbourhood change. Drawing from ethnographic research in the Latino barrios of North Denver, It deconstructs the history of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Other studies and essays have found parks in Latinx communities to be spaces for recreation, remembrance, cultural sovereignty, and collective resistance (Fernandez, Shinew, and Stodolska 2015; Flores‐Gonzalez 2001; Rinaldo 2002; Rodríguez‐Muñiz 2016; Rúa 2012; Suarez 1999). For example, Langegger's (1994, 2013b) study of a Latinx community garden in Denver found that public spaces, when properly appropriated, maintained, and developed, may act as a space for collective remembrance, helping to bridge the divide between the practices of Latinx residents and white newcomers and sustain culture even in the midst of gentrification surrounding the space.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies and essays have found parks in Latinx communities to be spaces for recreation, remembrance, cultural sovereignty, and collective resistance (Fernandez, Shinew, and Stodolska 2015; Flores‐Gonzalez 2001; Rinaldo 2002; Rodríguez‐Muñiz 2016; Rúa 2012; Suarez 1999). For example, Langegger's (1994, 2013b) study of a Latinx community garden in Denver found that public spaces, when properly appropriated, maintained, and developed, may act as a space for collective remembrance, helping to bridge the divide between the practices of Latinx residents and white newcomers and sustain culture even in the midst of gentrification surrounding the space.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although respondents in our study did not report negative perceptions of police, a study examining safety perceptions on a college campus found that female students reported actually feeling more fearful in the presence of police officers (Fisher & May, 2009). This may be particularly salient for people of color, as previous research has shown that they may avoid certain public spaces because of racial profiling or harassment from police or security guards (Langegger, 2013; Low, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies of diverse neighborhoods have often focused on public space, which is thought to promise equal access and provide opportunities for interaction with diverse others (Langegger ; Low et al. ).…”
Section: Diversity Conflict and Urban Public Spacementioning
confidence: 99%